PROPIEDADES FÍSICAS, HIDRÁULICAS Y MECÁNICAS DE SUELOS DE ORIGEN VOLCÁNICO, EN SITIOS SELECCIONADOS DEL VALLE CENTRAL, COSTA RICA - Mora Ch., Rolando (2011)
Four localities in Valle Central de Costa Rica have been selected to study the volcanic soils from a geo-technical point of view. The materials have been tested, measuring their physical, hidraulic and shear resistance properties, also incorporating results from other research works, trying to delimit their ranges of variation and the possibilities to use them as final places for deposition of solid waste. The soils have been studied with the help of the scan-ning elektron microscope, in order to interpret their macroscopic behavior by an microscopic approach.